Reconnecting Grazing Livestock to Crop Landscapes: Reversing Specialization Trends to Restore Landscape Multifunctionality - de Faccio Carvalho, Paulo César; de Albuquerque Nunes, Pedro Arthur; Pontes-Prates, Arthur; Szymczak, Leonardo Silvestri; de Souza Filho, William; Moojen, Fernanda Gomes; Lemaire, Gilles (Frontiers in Sustainable Food Systems, 2021)
Closely integrated crop and livestock production systems used to be the rule in agriculture before the industrial revolution. However, agricultural landscapes have undergone a massive intensification process in recent decades. This trajectory has led to uniform landscapes of specialized cropping systems or consolidated zones of intensive livestock production. Loss of diversity is at the core of increasing side effects on the environment from agriculture. The unintended consequences of specialization demand the reconciliation of food production with environmental quality. We argue that the reconnection of grazing livestock to specialized crop landscapes can restore decoupled biogeochemical cycles and reintroduce the necessary complexity to restore ecosystem functioning. Besides, the reconnection of crops and livestock promotes several ecosystem services underlying multifunctionality. We focus on the capacity of integrated crop-livestock systems to create biophysical and socioeconomic resilience that cope with weather and market oscillations. We present examples of redesigned landscapes that leverage grazing animals to optimize food production per unit of land while mitigating the externalities of specialized agriculture. We also debate mindset barriers to the shift of current specialization trends toward the design of multifunctional landscapes.